KEPASTIAN HUKUM PENGEMBALIAN LAHAN HAK GUNA USAHA DALAM UNDANG-UNDANG POKOK AGRARIA DI INDONESIA - Sati, Laras; Setyadji, Sri (Journal Evidence Of Law, 2022)
In the 1945 constitution it is stated that control over land is regulated by the state, thus all processes related to land, the state has a big role to play. The state has the highest legal authority in this matter. On the other hand, the customary community groups who inherit their lands also have a customary law system that regulates the issue of land ownership. Investors as shareholders in large-scale businesses do not dare to invest with such a land ownership pattern so that a regulation is needed that can guarantee the ownership status of these lands during the exploitation process. The government then formulated several legal regulations related to this matter. The core problem in this journal is how legal certainty is on lands that have been granted permits by the state for investment by companies and how certainty is in returning these lands to indigenous peoples. The purpose of this study is to explain the legal certainty of the land. The method used is a normative legal research method by examining the law and related regulations. The results found are that the state provides a strong guarantee for the return of community lands used for investment and the guarantee is contained in the basic national agrarian laws and regulations